2015
DOI: 10.1016/j.yebeh.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled multimodal behavioral intervention trial for improving antiepileptic drug adherence

Abstract: Purpose: Medication nonadherence is one of the most important reasons for treatment failure in patients with epilepsy. The present study investigated the effectiveness of a multicomponent intervention to improve adherence to antiepileptic drug (AED) medication in patients with epilepsy. Methods: In a prospective, randomized multicenter trial, three sessions of face-to-face motivational interviewing (MI) in combination with complementary behavior change techniques were compared with standard care. Motivational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
0
46
1
Order By: Relevance
“…Importantly, it has been shown that nearly 60% of patients could achieve seizure control by adhering to prescribed antiepileptic drugs (AEDs) [6]. However, it has been reported that 30%-50% of patients with epilepsy were nonadherent with their AED treatment schedules [7][8][9]. Thus, nonadherence is a critical issue for patients with epilepsy [10].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it has been shown that nearly 60% of patients could achieve seizure control by adhering to prescribed antiepileptic drugs (AEDs) [6]. However, it has been reported that 30%-50% of patients with epilepsy were nonadherent with their AED treatment schedules [7][8][9]. Thus, nonadherence is a critical issue for patients with epilepsy [10].…”
Section: Introductionmentioning
confidence: 99%
“…doubts about the need for AEDs, concerns about adverse effects and practical factors influencing medication taking have been emphasized recently (Chapman et al, 2014 andPakpour et al, 2015). Accordingly, the management should focus on the individual 40 non-adherence pattern, tailoring the intervention to the patient profile (Blaschke et al, 2012;Eatock and Baker, 2007).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…It is estimated that 70% of patients will respond to the medicines prescribed whilst the remainder will need surgery and other forms of therapy to achieve seizure control [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…AEs are contributors to poor drug compliance, which can be as high as 30% to 50% of adults living with epilepsy, low quality of life and drop outs from drug therapy [4,5,9]. AEs include neuropsychiatric, gastrointestinal, dermatological, endocrine and haematological side-effects.…”
Section: Introductionmentioning
confidence: 99%